Molecular Detection of Minimal Residual Cancer in Surgical Margins of Head and Neck Cancer Patients - A. Peggy Graveland; Michiel de Maaker; Boudewijn J. M. Braakhuis; Remco de Bree; Simone E. J. Eerenstein; Elisabeth Bloemena; C. René Leemans; Ruud H. Brakenhoff (Cellular Oncology)
A great disappointment in head and neck cancer surgery is that 10–30% of head and neck squamous cell carcinoma (HNSCC) patients develop local recurrences despite histopathologically tumor-free surgical margins. These recurrences result from either minimal residual cancer (MRC) or preneoplastic lesions that remain behind after tumor resection. Distinguishing MRC from preneoplasic lesions is important to tailor postoperative radiotherapy more adequately. Here we investigated the suitability of quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) using human Ly-6D (hLy-6D) transcripts as molecular marker to detect MRC in surgical margins.